PENERAPAN TEAMS GAMES TOURNAMENT (TGT) MELALUI MEDIA KARTU DOMINO PADA MATERI MINYAK BUMI SISWA KELAS XI MAN 4 ACEH BESAR - Susanna Susanna (UIN AR-RANIRY, 2017)
Actually, chemistry learning is very fun, but it takes a high motivation, passion and confident. Based on that, the teacher's effort in developing student's learning activity is very important, because the students' learning activity becomes the determinant of the success of learning that is done. The use of an appropriate learning methods was an alternative to overcome the problem of low absorption of students to the lesson. The arm of this research was to know how the applying of cooperative learning model Teams Games Tournament (TGT) was type through domino card media to affected the learning chemistry achievement of XI-MIA student in MAN 4 Aceh Besar. Instruments used i.e. research instruments and data instruments. Data collection techniques are observation, test results, and questionnaires. Based on the objectives and the results of data analysis in this study, shown that the teacher activity in managing learning for each cycle was in very good category. Student activity at the time of applying the cooperative learning model Teams Games Tournament (TGT) type through domino card media on petroleum material was active. Students' learning achievement after the implementation of Cycle I, cycle II and final test respectively was about 61.29%, 90.32% and 93.55%. Student response to the application of cooperative learning model type Teams Games Tournament (TGT) through domino card media on petroleum material was positive.